Vasorelaxing Action of the Kynurenine Metabolite, Xanthurenic Acid: The Missing Link in Endotoxin-Induced Hypotension? - Fazio, Francesco; Carrizzo, Albino; Lionetto, Luana; Damato, Antonio; Capocci, Luca; Ambrosio, Mariateresa; Battaglia, Giuseppe; Bruno, Valeria; Madonna, Michele; Simmaco, Maurizio; Nicoletti, Ferdinando; Vecchione, Carmine (Frontiers in Pharmacology, 2017)
The kynurenine pathway of tryptophan metabolism is activated by pro-inflammatory cytokines. L-kynurenine, an upstream metabolite of the pathway, acts as a putative endothelium-derived relaxing factor, and has been hypothesized to play a causative role in the pathophysiology of inflammation-induced hypotension. Here, we show that xanthurenic acid, the transamination product of 3-hydroxykynurenine, is more efficacious than L-kynurenine in causing relaxation of a resistance artery, but fails to relax pre-contracted aortic rings. In the mesenteric artery, xanthurenic acid enhanced activating phosphorylation of endothelial nitric oxide synthase (NOS), and the relaxing action of xanthurenic acid was abrogated by pharmacological inhibition of NOS and endothelial-derived hyperpolarizing factor (EDHF). Systemic injection of xanthurenic acid reduced blood pressure in mice, and serum levels of xanthurenic acid increased by several fold in response to a pulse with the endotoxin, lipopolysaccaride (LPS). LPS-induced hypotension in mice was prevented by pre-treatment with the kynurenine monooxigenase (KMO) inhibitor, Ro-618048, which lowered serum levels of xanthurenic acid but enhanced serum levels of L-kynurenine. UPF 648, another KMO inhibitor, could also abrogate LPS-induced hypotension. Our data identify xanthurenic acid as a novel vasoactive compound and suggest that formation of xanthurenic acid is a key event in the pathophysiology of inflammation-induced hypotension.